Dynamic loads indicators for take-off - landing sequence in blocks and attacks of elite female volleyball players - Kabacinski, J.; Dworak, L. B.; Murawa, M.; Rzepnicka, A. (Acta of Bioengineering and Biomechanics, 2016)
PURPOSE Dynamic loads during landings determined by the ground reaction forces (GRFs) may elaborate internal loads and increase the risk of overload knee injuries as a result of performing volleyball jumps many times. The study dealt with a biomechanical assessment of dynamic load indicators in female volleyball players for the motion sequence of take-off-landing in blocks and attacks. METHODS Twelve professional female volleyball players participated in the study. Blocks and attacks were filmed by two cameras. GRFs vs. time graphs were recorded with the use of a force platform. Values of dynamic load indicators in terms of the relations of peak of vertical component of GRF, build-up index of this force (BIF), and power output (P) during landing to the vGRF, BIF and P during take-off (L/T) were calculated. RESULTS The statistically significant ( p < 0.05) highest values of L/T indicators were found for back row attack spikes: 2.4 (vGRF), 12.2 (BIF) and 3.1 (P). In the case of blocks, slide attack spikes and attack line spikes, results of these variables were in range: 1.8÷2.1, 5.9÷7.6 and 2.1÷2.9, respectively. CONCLUSIONS The reduction of GRFs during landings contributes to decreasing the level of the load indicators L/T which should minimize the incidence of anterior cruciate ligament and patellar tendon injuries in female volleyball players.